Pengaruh Intensitas Menonton Program Youtube Channel Wirda Mansur terhadap Motivasi Membaca Al-Qur’an Subscriber - Nur Adilla Maulina; Nandang HMZ (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. The existence of mass media is very influential in everyday life. One of them is youtube. Youtube is a social media platform which provides various kinds of video content that is easy to access. Currently, there are many content creators who use YouTube as a medium for preaching, one of which is Wirda Mansur. There are so many youtube shows that motivate users or subscribers. This study focused on the effect of the intensity of watching YouTube on the motivation to read the Qur'an. Based on the description above, the problems in this research are formulated as follows: (1) How does the Youtube Chanel Wirda Mansur Program motivate in reading the Qur'an? (2) How is the intensity of watching Wirda Mansur's youtube channel program? (3) How does the intensity of watching Wirda Mansur's youtube channel program affect the motivation to read the Qur'an for subscribers? Researchers used quantitative methods. The population chosen in this study was Wirda Mansur's subscribers, which amounted to 1,042 million. With a 10% sampling technique the number of samples obtained was 110 respondents. The data collection technique used in this research is a questionnaire/ questionnaire. The analysis technique used in this research is descriptive. The results of this study are: the effect of watching intensity is influenced by motivation, activity duration, activity frequency, presentation, attitude and interest direction. The effect of the intensity of watching YouTube on the motivation to read the Qur'an is 14.20%. Abstrak. Keberadaan media massa sangat berpengaruh dalam kehidupan sehari-hari. Salah satunya adalah youtube. Youtube merupakan sebuah platform media sosial yang mana menyediakan berbagai macam content video yang mudah untuk diakses. Saat ini banyak sekali content creator yang memanfaatkan youtube sebagai media berdakwah salah satunya Wirda Mansur. Banyak sekali tayangan-tayangan youtube yang memotivasi para pengguna atau subscriber. Pada penelitian ini difokuskan terhadap pengaruh intensitas menonton youtube terhadap motivasi membaca Al-Qur’an. berdasarkan uraian diatas maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Bagaimana Program Youtube Chanel Wirda Mansur memotivasi dalam membaca Al-Qur’an? (2) Bagaimana intensitas menonton program youtube chanel Wirda Mansur? (3) Bagaimana pengaruh intensitas menonyon program youtube chanel Wirda Mansur terhadap motivasi membaca Al-Qur’an subscriber? Peneliti menggunakan metode kuantitatif. Populasi yang dipilih dalam penelitian ini adalah subscriber Wirda Mansur yang berjumlah 1.042 juta. Dengan teknik pengambilan sampel 10% jumlah sampel yang diperoleh sebanyak 110 orang responden. Teknik pengambilan data yang digunakan dalam penelitian ini adalah angket/kuisioner. Adapun teknik analisis yang digunakan dalam penelitian ini adalah deskriptif. Hasil dari penelitian ini adalah: pengaruh intensitas menonton dipengaruhi oleh motivasi, durasi kegiatan, frekuensi kegiatan, presentasi, arah sikap dan minat. Pengaruh intensitas menonton youtube terhadap motivasi membaca Al-Qur’an adalah 14,20%.